Perceptions of Arabic Language Education Students on the Implementation of an Innovative Curriculum | Tashawwurat tullab qism ta'lim al-lughah al-'Arabiyyah hawla tanfidh al-manhaj al-mubtakar - Huda, Hizbullah; Baihaqi, M.; Al Mubarak, Ahmad Jundi; Zaenuri, Muh; D, Habib; Solihah, Iis; Fatihuddin, Fatihuddin; Islam, Mohammed (Institut Agama Islam Negeri Palangka Raya, 2024)
The innovative curriculum is designed to better adapt to the needs of the working world and technological developments. This ensures that students not only acquire theoretical knowledge, but also the practical skills needed to succeed in their careers. It turns out that not all students understand the concept of the Independent Learning-Campus Independent Curriculum (innovative curriculum). On the other hand, students are not involved in the curriculum development process. This paper aims to describe student preparation in implementing an innovative curriculum, and reveal the impact of implementing an innovative curriculum. This type of research is qualitative research with a survey approach. The population of this study are students of the Arabic Language Education Study Program at UIN Sunan Ampel Surabaya who have used an innovative curriculum. The sample was drawn using purposive sampling technique. The instrument is a questionnaire that has been validated by two education experts. The conclusion of this study shows that students of the Arabic Language Education Study Program, UIN Sunan Ampel Surabaya have shown good readiness to implement an innovative curriculum. The research findings revealed that students felt an increase in their soft skills and hard skills. That is in the form of Arabic communication skills and the ability to master Arabic grammar, vocabulary, and Arabic sentence structure. This research makes a significant contribution to the development of higher education curriculum that the implementation of innovative curriculum effectively improves students' soft skills and hard skills.